In shade of Olympic glory: what should we know about female athletes triad? – a review - Anna Skoczek-Wojciechowska; Hubert Bochenek; Michał Bzoma; Julia Gugulska; Irmina Czerepak (Journal of Education, Health and Sport)
introduction and purpose: The numerous advantages of sport are widely known. Millions of children worldwide are encouraged to start training and significant part of them decide to start professional training. However, there are also certain health risk connected with intensive physical activity. One of them is female athletes triad – a syndrome consisting of three components: low energy availability (LEA), dysregulation of menstrual cycle and impaired bone mineral density (BMD).